Rutina de vida escolar y habilidades emprendedoras en estudiantes del quinto ciclo de la CEIPSMP Sagrada Familia 2023 - Morales Rios, Gianella Sorenghi (2024)
The findings of this study elucidate the relationship between the regimentation of school life and the cultivation of entrepreneurial skills among students in the fifth cycle at CEIPSMP Sagrada Familia in 2023. This exploration sought to understand how the structured routines of school life correlate with the development of entrepreneurial capabilities. The investigation encompassed a population of 159 students, employing a comprehensive census approach for the sample, and utilized surveys and questionnaires for data collection. The methodology adopted was relational, cross-sectional, field-oriented, and bivariate in nature. The conclusion drawn from the analysis posits a positive correlation between the structure of school life routines and the enhancement of entrepreneurial skills in students. This implies that students who are more actively engaged in structured school activities demonstrate an advanced proficiency in entrepreneurial skills, attributable to their engagement in environments that necessitate initiative, problem-solving, and collaborative efforts. Hence, fostering an environment that encourages a dynamic and enriched school routine emerges as crucial for nurturing entrepreneurial talents within the educational framework.